Bahan Ajar Bahasa Indonesia Tematik Berkarakter dan Berbudaya dengan Sastra Anak Bagi Siswa SD - Irawati, Retno Purnama (Jurnal Varidika: Varia Pendidikan, 2013)
The development of character values and cultural values is a long process start- ing from the initial incoming students to completion of an educational unit. In fact, the pro- cess starts from the kindergarten continues to elementary school and lasted at least until the 9th grade or last grade of junior high school. The development process of character and cultural values carried by each subject, and in each curricular and extracurricular activities, through all subjects, personal development, and education unit. This study seeks to describe the profile of Indonesian subjects teaching materials in the current elementary school according to teachers and students opinions and the needs of students and teach- ers towards Indonesian subjects thematic teaching materials which contains character and cultural values. Research and development is applied to the field of education . The subjects of research were elementary school students and elementary schools teachers in Ungaran and Semarang. 27 people (29 %) of teachers declared that there are Indonesian textbooks were still least helpful in teaching. 8 people (9 %) of teachers stated that the Indonesian textbooks were incomplete. 85 people (91 %) of teachers want the Indonesian textbook to be more complete, making it easier for teachers to teach.